Analisis Penetapan Harga Jual Produk Tahu Isi Pada Unit Usaha Koperasi (Studi Kasus Koperasi Sukuhale Kabupaten Gowa) - Baharuddin Baharuddin (Jurnal Online Manajemen ELPEI, 2022)
The purpose of this research is to analyze the selling price of tofu products in the Sukuhale cooperative business unit. As for what is used in data collection is sourced from the Sukuhale Cooperative, and field data directly. Based on the calculation of the selling price analysis for tofu products in the business unit of the Sukuhale Cooperative, the price applied by the Sukuhale Cooperative is Rp. selling for IDR 12,000, with the calculation of the desired profit of the cooperative being 15%, then using the method in this scientific work a price comparison of IDR 200 is found.